Choice of Inventory Accounting Methods: Comparative Analyses of Alternative Hypotheses - Lee, Chi-Wen Jevons; Hsieh, David A. (Journal of Accounting Research, 1985)
Inventory accounting method, Political costs, Agency costs, Production and investment characteristics